Japan's Remilitarization Struggle Since the Shinzo Abe’s Leadership - Muhammad Arif Prabowo (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
This article discusses Japan’s struggle to push its military capabilities to become more active in security issues since the reelection of Shinzo Abe in 2012. During this time, Japanese defense policy faced great challenges due to the restriction of the Japanese constitution of pacifism (Article 9) and the fact that the Japanese opposed the idea of militarism or ‘remilitarization’ initiated by Japanese political leaders, mainly Abe. However, the Chinese military presence in the region with overwhelming military capabilities and aggressive behavior, particularly around Diayou/Senkaku islands in the East China Sea, threatens Japan. This uncertainty has engendered a grim perception of China among the Japanese which forces Japan to fortify its security by reforming its defense policy to strengthen its military capabilities. In this essay, I argue that the remilitarization of Japan is stimulated by the Japanese perception of the threat of Chinese aggressiveness. By utilizing Robert Jervis's theory, the analysis is focused on a structural level to trace the incentive of Japan’s remilitarization. This security phenomenon will be enlightened by two imperative concepts of the security dilemma and perception of threat. Other domestic aspects like public opinion and elites are discussed to show the veracity of the main argument.